2014
DOI: 10.1016/j.clinimag.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical consequences of an indeterminate CT pulmonary angiogram in cancer patients

Abstract: Our aim was to evaluate clinical management and outcomes in cancer patients who had an indeterminate Computed Tomographic Pulmonary Angiogram (CTPA) for the assessment of pulmonary embolus. We reviewed 1000 CTPA studies and identified 251 limited (indeterminate) CTPA. We examined follow-up imaging and reviewed clinical management decisions and any positive diagnosis of venous thromboembolic disease (VTE) within the subsequent 90 days. 60 patients (23.9%) had a follow-up imaging study within five days. 8 had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Most of these patients had no further investigation as the referring clinicians treated indeterminate CTPA as an endpoint in their investigation. Hayes et al . with population group of oncology patients demonstrated that overall 82.5% of the indeterminate CTPA studies were interpreted as a negative result by the clinicians with only 23.9% undergoing further imaging to examine for venous thromboembolic disease within a 5‐day period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of these patients had no further investigation as the referring clinicians treated indeterminate CTPA as an endpoint in their investigation. Hayes et al . with population group of oncology patients demonstrated that overall 82.5% of the indeterminate CTPA studies were interpreted as a negative result by the clinicians with only 23.9% undergoing further imaging to examine for venous thromboembolic disease within a 5‐day period.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these patients had no further investigation as the referring clinicians treated indeterminate CTPA as an endpoint in their investigation. Hayes et al 9 with population group of oncology patients demonstrated that overall 82.5% of the indeterminate CTPA studies were interpreted as a negative result by the clinicians with only 23.9% undergoing further imaging to examine for venous thromboembolic disease within a 5-day period. It may be useful to gain insight into the clinician's understanding of 'indeterminate CTPAs' by conducting a survey among clinicians whether the decision to treat the CTPA as negative is due to clinical factors, or a misinterpretation of the radiology report.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 In the case of the V/Q scan, the degradation of the clinical utility of the test in the context of pre-existing or co-evolving lung disease presents a significant limitation. 38 This is further complicated by the significant presence of renal disease for CT angiography and lung disease for V/Q scans in the most at-risk populations for PE. Thus, in addition to improving these techniques, there remains significant interest in developing additional modalities for detection of clot.…”
Section: Pulmonary Embolusmentioning
confidence: 99%